Kritik Seni dengan Kasus Festival Seni Rupa “Nagari Ngayogyakarta Hadiningrat” - Hagung Kuntjara (Humaniora, 2013)
"War againt the forgot" – Some time ago the government through a bill drafted by the Ministry of Home Affairs rolled leadership succession issues covered in the bill of Privileges Yogyakarta which hands polemical dichotomy of choice 'Sultan is not automatically Governor' (by election) or 'Sultan is automatically Governor' (direct designation). Social and political conditions that nation endlessly polemical dichotomy is heating up at the public grassroot level to the national level lead to opposite parties and keep fire as unresolved. A Fine Arts Festival event titled "Nagari Ngayogyakarta Hadiningrat" one century to coincide with HB IX, was presented in Jogja National Museum (JNM) 13 April 2012 and 2 weeks later, became a kind of 'witness marker' of the existence and the constellation 'Nagari Yogyakarta Sultanate - HB IX' with the Republic of Indonesia. Form of attitudes, arts events as a marker – ‘Titi pranoto mongso’ - in ancient agrarian societies of Java was used as a natural event signs to be observed, the Arts Festival events can be read as a reminder to not forget, will conduct historical Yogyakarta. Practice of art criticism writing is about the Arts Festival event "Nagari Ngayogyakarta Hadiningrat" in the perspective of art criticism, which is not only a cultural festival article coverage of events, but also the existence of a strong side shoot 'Nagari Yogyakarta Sultanate - HB IX 'is presented in the form of representation of the works of art are very diverse and are free to respond to a given topic.